Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/cas.14101
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of transforming growth factor‐β‐Smads/microRNA‐362‐3p/CD82 mediated by M2 macrophages promotes the process of epithelial‐mesenchymal transition in hepatocellular carcinoma cells

Abstract: Abnormal tumor microenvironment and the epithelial‐mesenchymal transition (EMT) are important features of tumor metastasis. However, it remains unknown how signals can form complicated networks to regulate the sustainability of the EMT process. The aim of our study is to explore the possible interaction between tumor‐associated macrophages and tumor cells in the EMT process mediated by microRNA (miR)‐362‐3p. In this study, we found that by releasing TGF‐β, M2 macrophages mediate binding of Smad2/3 to miR‐362‐3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…Surface proteins, such as CD206 (mannose receptor-1), CD204 and CD163 (macrophage scavenger receptors), are also overexpressed ( 28 ). These M2-like TAMs have critical roles in facilitating epithelial-mesenchymal transition (EMT), angiogenesis and immunosuppression ( 29 , 30 ). Moreover, M2-like TAMs are one of the factors hampering the efficacy of chemotherapy and radiotherapy through suppression of CD8 + T cell function, leading to tumor progression and poor outcomes ( 28 , 31 , 32 ).…”
Section: Characteristics Of Tamsmentioning
confidence: 99%
“…Surface proteins, such as CD206 (mannose receptor-1), CD204 and CD163 (macrophage scavenger receptors), are also overexpressed ( 28 ). These M2-like TAMs have critical roles in facilitating epithelial-mesenchymal transition (EMT), angiogenesis and immunosuppression ( 29 , 30 ). Moreover, M2-like TAMs are one of the factors hampering the efficacy of chemotherapy and radiotherapy through suppression of CD8 + T cell function, leading to tumor progression and poor outcomes ( 28 , 31 , 32 ).…”
Section: Characteristics Of Tamsmentioning
confidence: 99%
“…9,10 Recent studies demonstrate that S100A9 could promote growth and metastasis of HCC cells. 11,12 Previous studies have revealed the cross talk between TAMs and cancer cells in HCC through soluble factors, including transforming growth factor-β (TGF-β), 13 hepatocyte growth factor 14 and IL-6. 15 These factors secreted from TAMs could promote the tumor progression by activating intrinsic signaling pathways of cancer cells, which are associated with epithelialmesenchymal transition, drug resistance and stemness.…”
mentioning
confidence: 99%
“…Furthermore, there are other precedents of miRNA positive regulation of the EMT process via feedback, double feedback or forward-feed loops between miRNAs and the targets, such as SNAI1 and E-cadherin (reviewed in 26 , 27 ). Zhang et al (2019) 49 have recently shown that the SMAD2/3 complex binds to the promoter of the miR-362 gene to positively regulate miR-362 expression (Fig. 6 A, blue lines).…”
Section: Discussionmentioning
confidence: 91%